Atypical Manifestations of Cutaneous Leishmaniasis in a Region Endemic for Leishmania braziliensis: Clinical, Immunological and Parasitological Aspects. - Luiz Henrique Guimarães; Adriano Queiroz; Juliana A Silva; Silvana C Silva; Viviane Magalhães; Ednaldo L Lago; Paulo Roberto L Machado; Olívia Bacellar; Mary E Wilson; Stephen M Beverley; Edgar M Carvalho; Albert Schriefer (Public Library of Science (PLoS), 2016)
BACKGROUND:Atypical cutaneous leishmaniasis (ACL) has become progressively more frequent in Corte de Pedra, Northeast Brazil. Herein we characterize clinical presentation, antimony response, cytokine production and parasite strains prevailing in ACL. METHODOLOGY/PRINCIPAL FINDINGS:Between 2005 and 2012, 51 ACL (cases) and 51 temporally matched cutaneous leishmaniasis (CL) subjects (controls) were enrolled and followed over time in Corte de Pedra. Clinical and therapeutic data were recorded for all subjects. Cytokine secretion by patients' peripheral blood mononuclear cells (PBMC) stimulated with soluble parasite antigen in vitro, and genotypes in a 600 base-pair locus in chromosome 28 (CHR28/425451) of the infecting L. (V.) braziliensis were compared between the two groups. ACL presented significantly more lesions in head and neck, and higher rate of antimony failure than CL. Cytosine-Adenine substitutions at CHR28/425451 positions 254 and 321 were highly associated with ACL (p<0.0001). In vitro stimulated ACL PBMCs produced lower levels of IFN-γ (p = 0.0002) and TNF (p <0.0001), and higher levels of IL-10 (p = 0.0006) and IL-17 (p = 0.0008) than CL PBMCs. CONCLUSIONS/SIGNIFICANCE:ACL found in Northeast Brazil is caused by distinct genotypes of L. (V.) braziliensis and presents a cytokine profile that departs from that in classical CL patients. We think that differences in antigenic contents among parasites may be in part responsible for the variation in cytokine responses and possibly immunopathology between CL and ACL.